Creación de universo gráfico para la marca Solearte: manual de identidad visual y redes sociales - Jabbour Reyes, Romina Harisa (2023)
This present communicative project consists of a series of illustrations created by the artist Romina Jabbour to be disseminated on social networks, starting with Instagram. The work as a whole is intended to be gathered around a new brand called Solearte, a company that will organize and market the pictorial works of the artist as well as their application in various products. The project also considers the design of a visual identity manual with the aim of organizing and systematizing the graphic ecosystem created by the artist and promoting the brand's personality. This personality revolves around a Danish concept called Hygge, which describes the appreciation of simplicity and happiness in everyday things. This philosophy is revealed with the management of secondary and tertiary colors, the clean lines and shapes and the tenderness of the atmospheres and characters, graphic qualities that seek to generate feelings of happiness and joy. In conclusion, the graphic world of Solearte, created by artist Romina Jabbour, is a communicative project that invites us to appreciate the small pleasures of life and to generate a feeling of gratitude for a visual environment of well-being and satisfaction.